2004
DOI: 10.1111/j.1462-5822.2004.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

The major outer sheath protein of Treponema denticola inhibits the binding step of collagen phagocytosis in fibroblasts

Abstract: SummaryBacterial infections contribute to the chronicity of connective tissue lesions in part by perturbing extracellular matrix remodelling processes. We examined a novel mechanism by which the major outer sheath protein (Msp) of the spirochaete Treponema denticola

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
60
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 51 publications
2
60
1
Order By: Relevance
“…This finding is consistent with studies of Msp-treated fibroblasts (15,27) and T. denticola-treated KB epithelial cells (6), target cells that undergo gross cytoskeletal reorganization but remain viable. Enriched Msp is also known to depolarize HeLa cell membranes, presumably by establishing short-lived ion channels (13).…”
supporting
confidence: 90%
See 3 more Smart Citations
“…This finding is consistent with studies of Msp-treated fibroblasts (15,27) and T. denticola-treated KB epithelial cells (6), target cells that undergo gross cytoskeletal reorganization but remain viable. Enriched Msp is also known to depolarize HeLa cell membranes, presumably by establishing short-lived ion channels (13).…”
supporting
confidence: 90%
“…Yet there is little knowledge of the T. denticola factors that may modulate key antimicrobial pathways and mechanisms in PMNs. The crucial role of the cytoskeleton in migration and endocytosis, combined with previous findings that the major outer sheath protein (Msp) of T. denticola perturbed actin assembly in fibroblasts (1,15,27), suggested that Msp may modulate human neutrophil chemotaxis and phagocytosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The 53-kDa major surface protein (Msp) of T. denticola ATCC 35405 has been shown to have pore-forming and adhesion activities (13,30). This protein also inhibits agonist-induced Ca 2ϩ release from the internal stores by uncoupling the storeoperated channels (52) and the binding step of collagen phagocytosis in gingival fibroblasts (3). Dentilisin having chymotrypsin-like activity has been found to be located in the outer membrane (10).…”
mentioning
confidence: 99%